2015
DOI: 10.1111/puar.12442
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Local Economic Structure on Community Philanthropy

Abstract: This article explores how local economic structure directly and indirectly affects community philanthropy. Drawing on campaign data for local United Way (UW) affiliates at three points in time (1990, 2000, and 2010), the article tests the degree to which the relationship between economic structure and community philanthropy is mediated through local stocks of human resources and social capital. The results suggest that retail employment and industrial concentration negatively affect local UW campaigns, while n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 56 publications
(90 reference statements)
1
22
1
1
Order By: Relevance
“…Saxton and Benson () found that the growth of the nonprofit sector is positively related to the level of social capital in the community. Paarlberg and Yoshioka () also found a positive correlation between social capital and community philanthropy. Nonprofits are not only influenced by the level of social capital in a community.…”
Section: Determinants Of Nonprofits' Involvement In the Cogovernance mentioning
confidence: 88%
See 1 more Smart Citation
“…Saxton and Benson () found that the growth of the nonprofit sector is positively related to the level of social capital in the community. Paarlberg and Yoshioka () also found a positive correlation between social capital and community philanthropy. Nonprofits are not only influenced by the level of social capital in a community.…”
Section: Determinants Of Nonprofits' Involvement In the Cogovernance mentioning
confidence: 88%
“…Without committed residents in the community and a certain level of community stability, it is very challenging for nonprofits to stay through this complicated process. The local homeownership rate is often used in previous literature as indicators of community stability and citizens' long‐term commitment to the community (Paarlberg and Yoshioka ).
Hypothesis 2: The likelihood of a nonprofit's involvement in public service planning and design is positively correlated with the stability of the community in which the nonprofit operates.
…”
Section: Determinants Of Nonprofits' Involvement In the Cogovernance mentioning
confidence: 99%
“…Globalizing/devolutionary forces have increasingly led to local governments retreating from direct service provision, shifting the burden of community welfare to nonprofits and private organizations in the “neoadministrative” state (Durant ; Howlett ; Kettl ; Milward and Provan ; Sclar ). The economic structure of a local market also impacts community policy capacity (Paarlberg and Yoshioka ). By shifting problem‐solving burdens from governments to private actors, communities, and individuals, civic engagement, or collectively working to solve community problems, becomes all the more important.…”
Section: Globalization Devolution and Civic Welfarementioning
confidence: 99%
“…As such, the capacity of a community to respond to local needs has been a subject of discussion in public administration for several decades (Wolch ), and concern over this “uneven capacity” has been reiterated recently (Paarlberg and Yoshioka ). Public administration scholars have suggested that connecting elected leadership, bureaucratic management, and an engaged public is one of the primary challenges to effective governance in the coming decades.…”
Section: Globalization Devolution and Civic Welfarementioning
confidence: 99%
“…Therefore, federal expenditure in each county is necessary to control for the size of government (Grønbjerg and Paarlberg 2001;Lecy and Van Slyke 2013) and to estimate the effects of government expenditures in the nonprofit sector (Paarlberg and Yoshioka 2016). The data is obtained from the Census's USA Counties database.…”
Section: Gdp It =mentioning
confidence: 99%